(untitled) (Annual of the Faculty of Philosophy in Skopje, 2025)
For more than three decades, the stress generation hypothesis has inspired indepth study of the relationship between psychopathological phenomena and stressful experiences. The model proposes that in individuals already struggling with significant mental health problems, certain personality, cognitive, and interpersonal vulnerability factors lead to experiencing a higher rate of stressful life events. Initially, the hypothesis was proposed in relation to depression, but it was later associated with other mental disorders as well. Unlike dominant assumptions about the relationship between stress and psychopathology, this model highlights the active role that individuals play in shaping their life circumstances. This generated, so-called, dependent stress is both an outcome (at least partly) of impaired mental health, as well as a mechanism that maintains or exacerbates psychological dysfunctions. The paper presents a brief review of empirical findings that support the transdiagnostic utility of the model and provide insight into risk factors for stress generation. Clinical implications relevant to the treatment of impaired mental health are discussed, along with methodological limitations and recommendations, as well as directions for future research.